Ritual Killings, Badoo Phenomenon, and the Socio-Economic Consequences in Ikorodu Local Government Area of Lagos State, Nigeria - BOGE, Faruq Idowu (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2021)
This article is a microcosmic study of crimes and criminalities in Lagos State, Nigeria. In the lights of the contemporary social problems and criminalities bedevilling the global space, the article examines the emergence and peculiar modus operandi of a notorious ritualist’s gang known as “Badoo” within the Ikorodu Local Government Area (LGA) of Lagos State. It investigates the impacts of the activities of the dreaded group on the social and economic fabrics of Ikorodu LGA in the face of the prevailing security challenges in Nigeria. The study adopts the historical and qualitative research methodologies where media reports, internet materials, interviews, personal observations, and extant literatures are collated for critical analysis. In conclusion, the study asserts that the activities of the ritualist gang were seemingly unprecedented in nature and character. It affected the socio-economic and security frameworks of the Ikorodu LGA and Lagos State, during the period of the rampage.